(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The intention of this paper is to bring out the advantages of mobile gamification in learning English language. The gift of 21st century is the advancement in technology and the development of novel language learning methods and techniques. This study investigates the recent trend of learning English language through mobile gamification. This modern era is a birthplace for many new-flanged English language teaching technological apparatus. The eventual purpose of this paper is to throw light upon the gaming applications and its effectiveness in teaching and learning English language.